Pressure Pain Sensitivity in Patients With Suspected Opioid-Induced Hyperalgesia. Issue 6 (1st November 2015) - Wasserman, Ronald A.; Hassett, Afton L.; Harte, Steven E.; Goesling, Jenna; Malinoff, Herbert L.; Berland, Daniel W.; Zollars, Jennifer; Moser, Stephanie E.; Brummett, Chad M.
Abstract : Background and Objectives: This study was designed to test whether a brief quantitative sensory testing assessment could be used to detect hyperalgesia in patients with suspected opioid-induced hyperalgesia (OIH). Methods: Twenty patients on long-term opioid therapy with suspected OIH were recruited along with 20 healthy controls. Pressure pain threshold, Pain50, a measure of intermediate suprathreshold pressure pain sensitivity, and tolerance levels were evaluated. As a secondary outcome, changes in pressure pain sensitivity after intravenous administration of placebo (saline) and fentanyl (1.5 μg/kg) were assessed. Results: There were no significant differences in pain measures between healthy controls and patients. However, there was an association between higher doses of opioids and having a lower pain tolerance ( r = −0.46, P = 0.041) and lower Pain50 ( r = −0.46, P = 0.044), which was consistent with the hypothesis. Patients on more than 100 mg oral morphine equivalents displayed decreased pressure pain tolerance compared with patients taking less than 100 mg oral morphine equivalents ( P = 0.042). In addition, male patients showed a hyperalgesic response to fentanyl administration, which was significant for the Pain50 measure ( P = 0.002). Conclusions: Whereas there were no differences between patients suspected of having OIH and the healthy controls, the finding that higher doses of opioids were associated with more sensitivity suggests that dose might be an important factor in the development of hyperalgesia. In addition, male patients demonstrated a hyperalgesic response after a bolus of fentanyl. Future studies are needed to develop better diagnostics for detecting hyperalgesia in the clinical setting.